Customer Relationship Management System at Aesthetic Clinic - nina fadilah najwa; Muhammad Ariful Furqon; Yosari Dwi Fadhillah (Politeknik Caltex Riau, 2023)
Accessing and processing information more effectively and efficiently is made possible through the employment of quality information technology, one of which is in the technology the clinic requires. According to our case study, the clinic is still manually documenting customer service data and experiencing declining repeat client visits. Utilizing information technology is necessary for efforts to boost customer value innovation. As one of its aspects, Customer Relationship Management uses a framework of dynamics to acquire customer satisfaction data from loyal customers. The utilization of customer data will be categorized into platinum, gold, and silver using a ranking system for decision-making with the Simple Additive Weighting method—rating customers through the normalization of a decision matrix. The maximum consumer value based on the parameters determined by the choice matrix is one, while the lowest is 0.27. The testing that has been conducted is black-box testing. It is determined that 100 percent of the system's functionality is operating correctly, and UAT testing reveals that all features operate properly. Usability Testing conducted on patients yielded a ratio of 78.1%, indicating that the clinic evaluated customer satisfaction with the customer relationship management system.